PENGARUH PEMBERIAN KOMPENSASI DAN MOTIVASI KERJA TERHADAP EFEKTIVITAS KERJA KARYAWAN PADA PT BATIK DEWI BROTOJOYO TAHUN 2015 - Mulyati Mulyati (EQUILIBRIUM : Jurnal Ilmiah Ekonomi dan Pembelajarannya, 2016)
This study aims to: 1) determine whether there is a significant influence on the effectiveness of the compensation of employees in the batik industry Goddess Brotojoyo2015; 2) determine whether there is a significant influence on the effectiveness of work motivation of employees at Industry batik Dewi Brotojoyo 2015; 3) determine whether there is a significant effect compensation and work motivation on the effectiveness of employees in the batik industry Goddess Brotojoyo 2015. The population was are all employees of Industry Batik Dewi Brotojoyo in Masaran, some 225 employee. Method sampling technique used is produce random sampling proportional sample of 45 responden. Method analysis used in this study is the linear regression analysis ganda. Result tests performed showed that percentage physical work environment at PT. Batik Dewi Brotojoyo Masaran2015 amounted to 76.8%, the compensation amounting to 76.98%, and the effectiveness of employees amounted to 78.43%. From the calculation, the regression equation 9.766 + 0.228X1  + 0.345 X2. This means that the average effectiveness of employees (Y) is expected to increase or decrease by 0.228 for every one unit increase or decrease in the work environment and would have increased or decreased by 0.345 for every one unit increase or decrease the compensation.